St. Peter's, Theberton, Suffolk in the diocese of Saint Edmundsbury & Ipswich (Record of Church Furnishings, 1992)
Keywords: theberton

Profeßbücher bayerischer Prämonstratenserklöster: Osterhofen - Backmund, Norbert; Lickleder, Hermann (Deggendorfer Geschichtsblätter, 1992)
Keywords: osterhofen

Les manuscrits médiévaux de l'Abbaye de Parc. Recueil d'articles - Balberghe, Emile van (Documenta et opuscula, 1992)
Keywords: park

Einige Zwischenergebnisse von der Wüstungsgrabung "Kloster Barthe" im Heseler Wald, Ldkr. Leer - Bärenfänger, Rolf (Nachrichten aus Niedersachsens Urgeschichte, 1992)
Keywords: barthe

The Libraries of the Cistercians, Gilbertines, and Premonstratensians - Bell, David N. (Corpus of British medieval library catalogues, 1992)
Keywords: 🇬🇧 great britain (general)

Die Renovierung der Propsteikirche St. Walburga zu Werl im Jahre 1988. - Best, Gerhard; Halekotte, Theo (Alte und neue Kunst, 1992)
Keywords: werl

L'abbaye prémontrée de Lahonce - Biard, Georges (Les femmes dans l'orde de Prémontré, les abbayes de la cicarie de Gascogne. Actes Officiels du 17ème Colloque du C.E.R.P. (Valmont, 1992), 1992)
Keywords: lahonce

Flaesheim. Prämonstratenserinnen - Burghardt, Werner (Westfälisches Klosterbuch. Lexikon der vor 1815 errichteten Stifte und Klöster von ihrer Gründung bis zur Aufhebung, 1992)
Keywords: flaesheim

Sainte-Marie d'Arthous - Cabanot, Jean (La Gascogne romane, 1992)
Keywords: arthous

Brevnov a Strahov na pocátku 15. století - Čechura, Jaroslav (Historia docet. Sborník prací k pocte sedesátych narozenin prof. PhDr. Ivana Hlavácka, 1992)
Keywords: strahov

Himmelpfortkloster - Czeike, Felix (Historisches Lexikon Wien in 5 Bänden, 1992)
Keywords: himmelspforte (austria)

Notre-Dame de Dilo : une abbaye au coeur du pays d'Othe (1132-1790) - Dauphin, Jean-Luc (Terre d'histoire, 1992)
Keywords: dilo

Norbert von Xanten bei Propst Richer im Regularkanonikerstift Klosterrath - Deutz, Helmut (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

"Das Rohttahl im Landkapitel Dietenheim". Beiträge zur Geschichte der Prämonstratenser-Reichsabtei Rot und der Pfarreien Haslach, Rot an der Rot und Steinhausen an der Rottum - Diemer, Kurt (BC-Heimatkundliche Blätter für den Kreis Biberach, 1992)
Keywords: rot an der rot

Zunächst wurden ausschließlich adelige Damen hier aufgenommen: aus der Geschichte des früheren Klosters Wirberg - Dietz, Erich (Heimat im Bild. Beilage des Gießener Anzeiger, 1992)
Keywords: wirberg

Aux origines du "Jardin Clos" à Herentals (1410): la situation juridique d'une communauté de l'ordre de Prémontré au XVe siècle - Dijck, Leo van (Actes officiels du 17ème Colloque du Centre d'études et de recherches prémontrées : Prieuré du Béarn, Valmont, 1991 : les femmes dans l'ordre de Prémontré, les abbayes de la circarie de Gascogne, 1992)
Keywords: herentals

Kloster Mildenfurth/Thüringen: zur Baugeschichte, zu den Quellen und zum Forschungsstand - Eichhorn, Herbert (Der Landkreis Gera, 1992)
Keywords: mildenfurth

Bernard et Norbert: eschatologie et reforme - Goetz, H.W. (Bernard de Clairvaux : histoire, mentalités, spiritualité, 1992)
Keywords: 👤 norbert of xanten

La Orden Premonstratense en España: el Monasterio de Santa María de Aguilar de Campoo (siglos XI-XV) - González de Fauve, María Estela (Centro de Estudios del Románico, 1992)
Keywords: aguilar de campoo

Heeft Norbert in 1113/1114 de bisschopszetel van Kamerijk geweigerd? - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Norbert als kapelaan van Frederik I van Keulen, 1112 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Norbert als vredesapostel te Fosses, Moustier, Gembloers en Corroy-le-Château, 1119 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Norbert en de stichting van Cappenberg, 1122 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: cappenberg; 👤 norbert of xanten

Norbert op het concilie von Reims in oktober 1119 - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1992)
Keywords: 👤 norbert of xanten

Abbaye de Postel à Mol - Hermans, J. (Monasticon Belge. Bd. 8: Province d'Anvers, 1992)
Keywords: postel

Elementos tardorrománicos en la iglesia de Santa María la Real de Aguilar de Campoo (Palencia) - Hernando Garrido, José Luis (II Curso de cultura medieval : Aguilar de Campoo, 1-6 octubre 1990 : seminario, 1992)
Keywords: aguilar de campoo

Sobre los capiteles procedentes de la Iglesia del Monasterio de Sta. María la Real de Aguilar de Campoo (Palencia) conservados en el Museo Arqueológico Nacional - Hernando Garrido, José Luis (Boletín del Museo Arqueológico Nacional, 1992)
Keywords: aguilar de campoo

L’abbaye de Sainte-Marie de Mureau de l’ordre de Prémontré au XIIe et XIIIe siècle; étude du temporel abbatial - Hilaire, Guy (Université de Lorraine, 1992)
Keywords: mureau

Die Prämonstratenserklöster Churwalden und St. Jakob im Prättigau. Wirtschaftliche Entwicklung und Kolonisationstätigkeit - Hitz, Florian (Bündner Monatsblatt, 1992)
Keywords: churwalden; prättigau

Wirtschaftsweise und Kolonisationstätigkeit der Praemonstratenserklöster Churwalden und St. Jakob im Prättigau - Hitz, Florian (Das Werk der Klöster bei der Besiedlung der Alpen : Akten der VIII. internationalen Walser Studientagung in Brig, Naters un Simplon, 14. - 15. september 1990, 1992)
Keywords: churwalden; prättigau

Das Ankunftsbuch des Klosters Windberg - Hopfenmüller, Friedrich (Ludwig-Maximilians-Universität, 1992)
Keywords: windberg

Prieuré de Leliëndaal à Hombeek, puis à Malines - Houtman, Erik (Province d'Anvers, 1992)
Keywords: leliëndaal

Prieuré Het Besloten Hof à Herentals - Houtman, Erik (Monasticon Belge. Bd. 8: Province d'Anvers, 1992)
Keywords: herentals

Wezemaal en de Norbertijnen - Humblé, Louis (Tijdingen van het Beatrijsgezelschap, 1992)
Keywords: wezemaal

'Sancti Nicolai de Fontibus Amoenis' or 'Sti. Nicolai et Fontium Amenorum': The Making of Monastic History - Husband, Timothy (The Cloisters: Studies in Honor of the Fiftieth Anniversary, 1992)
Keywords: bellpuig de las avellanes

Olavsklosteret i Tønsberg: Nordens største rundsmie - Jahnssen, Lasse (Vestfoldminne, 1992)
Keywords: tønsberg

Die religiöse und kulturelle Bedeutung der Abtei Steinfeld in der Eifel - Joester, Ingrid (Geschichte im Bistum Aachen, 1992)
Keywords: steinfeld

Kloster Niederehe in der Gemeinde Üxheim (Eifel) - Kees, Peter (Rheinische Kunststätten, 1992)
Keywords: niederehe

Die Klosterkirche von Churwalden. Ausgrabungen und Bauuntersuchungen - Keller, Béatrice (Archäologie in Graubünden : Funde und Befunde ; Festschrift zum 25jährigen Bestehen des Archäologische Dienstes Graubünden, 1992)
Keywords: churwalden

Hermannus Judaeus's Opusculum: in defence of its authenticity - Kleinberg, Aviad M. (Revue des Etudes Juives, 1992)
Keywords: 👤 hermann of cologne

Elsey. Prämonstratenserinnen - Klueting, Edeltraud (Westfälisches Klosterbuch. Lexikon der vor 1815 errichteten Stifte und Klöster von ihrer Gründung bis zur Aufhebung, 1992)
Keywords: elsey

Keppel. Prämonstratenserinnen - Klueting, Edeltraud (Westfälisches Klosterbuch. Lexikon der vor 1815 errichteten Stifte und Klöster von ihrer Gründung bis zur Aufhebung, 1992)
Keywords: keppel

Bredelar. Prämonstratenserinnen, dann Zisterzienser - Klueting, Harm (Westfälisches Klosterbuch. Lexikon der vor 1815 errichteten Stifte und Klöster von ihrer Gründung bis zur Aufhebung, 1992)
Keywords: bredelar

Abbaye de Tongerlo - Koyen, Milo Hendrik; Dyck, Leo Cyriel van (Province d'Anvers, 1992)
Keywords: tongerlo

Hermann Josef von Steinfeld (um 1160 - 1241) im Kontext christlicher Mystik - Kugler, Hermann J. (EOS-Verl., 1992)
Keywords: 👤 hermann joseph of steinfeld

Confronting the otherness of the Greeks: Anselm of Havelberg and the division between Greeks and Latins - Lees, Jay Terry (Analecta Praemonstratensia, 1992)
Keywords: 👤 anselm of havelberg

Emo: didacticus en moralist. Beschouwing naar aanleiding van de nieuwe editie van de kroniek van Bloemhof - Lemmers, G. (Analecta Praemonstratensia, 1992)
Keywords: bloemhof

Steinfeld und die Gründung von Strahov (1142/43). Wann wurde Steinfeld prämonstratensisch? - Löhnertz, Werner (Analecta Praemonstratensia, 1992)
Keywords: steinfeld; strahov

Die Erwerbspolitik der Abtei Prémontré unter Norbert von Xanten und Hugo von Fosse (1120-1161) - Lohrmann, Dietrich (Erwerbspolitik und Wirtschaftweise mittelalterlicher Orden und Klöster, 1992)
Keywords: prémontré; 👤 hugh of fosses

De Liturgische handschriftenfragmenten met muzieknotatie van Abdij van Berne - Loos, I. de (Rijksuniversiteit Utrechet, 1992)
Keywords: berne; 🎶 musicology

Santa María la Real d'Aguilar de Campóo (Palencia) i altres esglésies romàniques de la província - López Gómez, Annabel (Circular d'Amics de l'Art Romànic, 1992)
Keywords: aguilar de campoo

Ist Hermann von Schedas Opusculum de conversione sua eine Fälschung? - Lotter, Friedrich (Aschkenas: Zeitschrift für Geschichte und Kultur der Juden, 1992)
Keywords: 👤 hermann of cologne

Pour une histoire authentique de l'abbaye du Lac de Joux - Martinet, Claire (University of Lausanne, 1992)
Keywords: lac de joux

The monastery of Santa Maria la Real (Aguilar de Campoo, Palencia): archaeology and architecture - Matesanz Vera, Pedro (Religion and belief : a Conference on Medieval Archaeology in Europe, 21-24th September 1992 at the University of York, 1992)
Keywords: aguilar de campoo

Clarholz. Prämonstratenser - Meier, Johannes (Westfälisches Klosterbuch, 1992)
Keywords: clarholz

Lette. Prämonstratenserinnen - Meier, Johannes (Westfälisches Klosterbuch. Lexikon der vor 1815 errichteten Stifte und Klöster von ihrer Gründung bis zur Aufhebung, 1992)
Keywords: lette

Die Meerer Hofesgüter im ehemaligen Amt Lank – Der Werthhof in Nierst - Meyer-Rogmann, Vera (Meerbuscher Geschichtshefte, 1992)
Keywords: meer

Identification des notables de l'Avranchin et du Cotentin cités dans le Livre noir de l'abbaye de la Lucerne: (1143-1309) - Mons de Carantilly, Rodolphe de (Publications multigraphiées de la Société d'archéologie et d'histoire de la Manche, 1992)
Keywords: la lucerne

Marchtal: Prämonstratenserabtei, fürstliches Schloss, kirchliche Akademie : Festgabe zum 300jährigen Bestehen der Stiftskirche St. Peter und Paul (1692-1992) - Müller, Max; Reinhardt, Rudolf; Schöntag, Wilfried (Süddeutsche Verlagsgesellschaft, 1992)
Keywords: marchtal

Die Klausur des ehemaligen Prämonstratenserklosters Jerichow - Naumann, Rolf (Große Baudenkmäler, 1992)
Keywords: jerichow

El monasterio premostratense de Bujedo (Burgos) y la nueva traza del convento en 1583 - Ordax, Salvador Andrés (Boletín del Seminario de Estudios de Arte y Arqueología, 1992)
Autoría: Salvador Andrés Ordax. Localización: Boletín del Seminario de Estudios de Arte y Arqueología: BSAA. Tomo 58, 1992. Artículo de Revista en Dialnet.
Keywords: bujedo de candepajares

Ein Prämonstratenser am Konzil von Konstanz (1414-1418)? - Pichler, Isfried Hermann (Analecta Praemonstratensia, 1992)
Keywords: 📚 premonstratensian (general)

L'abbaye Sainte-Marie de Chartreuve aux Dames - Plouvier, Martine (Les femmes dans l'Ordre de Prémontré ; Les abbayes de la circarie de Gascogne: actes officiels du 17e Colloque du Centre d'études et de recherches prémontrées, prieuré du Béarn, Valmont, [Montaut], [10-13 octobre] 1991, 1992)
Keywords: chéry-chartreuve

Berentrop. Prämonstratenser - Potthoff, Marie-Theres (Westfälisches Klosterbuch. Lexikon der vor 1815 errichteten Stifte und Klöster von ihrer Gründung bis zur Aufhebung, 1992)
Keywords: berentrop

Profeßbuch des Stiftes Schlägl: eine Festgabe zum 775. Bestandsjubliäum des Stiftes Schlägl (1218 - 1993) - Pröll, Laurenz (Schlägler Schriften, 1992)
Keywords: schlägl

K dějinám česko-polských vztahů ve středověku. (Šlechta a premonstráti ve 12. století.) - Rajman, Jerzy (Mediaevalia historica Bohemica, 1992)
Keywords: 🇨🇿 czechia (general); 🇵🇱 poland (general)

Początki opactw norbertańskich w Strahowie i Brzesku - Rajman, Jerzy (Nasza Przeszłość, 1992)
Keywords: brzesko

Średniowieczne zapiski w nekrologu klasztoru norbertanek na Zwierzyńcu - Rajman, Jerzy (Nasza przeszlosc, 1992)
Keywords: zwierzyniec

Cappenberg-Prämonstratenser - Reimann, Norbert (Westfälisches Klosterbuch, 1992)
Keywords: cappenberg

Dortmund. Prämonstratenserinnen, gen. das Katharinenkloster - Reimann, Norbert (Westfälisches Klosterbuch. Lexikon der vor 1815 errichteten Stifte und Klöster von ihrer Gründung bis zur Aufhebung, 1992)
Keywords: dortmund

Das Prämonstratenserkloster Speinshart - Reiß, Gerhard (Der Eisenbahnergenealoge, 1992)
Keywords: speinshart

Los Premonstratenses y su arquitectura: Historia de un olvido - Sanz, Maria Teresa López de Guereño (Anuario del Departamento de Historia y Teoría del Arte, 1992)
Los Premonstratenses y su arquitectura: Historia de un olvido
Keywords: 🇪🇸 spain (general)

Cappel. Prämonstratenserinnen - Schneider, Manfred (Westfälisches Klosterbuch. Lexikon der vor 1815 errichteten Stifte und Klöster von ihrer Gründung bis zur Aufhebung, 1992)
Keywords: cappel

The Premonstratensians in the Crusader Kingdoms in the Twelfth and Thirteenth Centuries - Slack, Corliss Konwiser (Analecta Praemonstratensia, 1992)
Keywords: 🌐 latin east (general)

Jeszcze o dokumentach fundacyjnych klasztoru premonstratensów w Grobe - Stróżyk, Paweł (Roczniki Historyczne, 1992)
Encore une fois des documents de fondation du monastère des prémontrés à Grobe
Keywords: grobe

On the technology and assortment of the medieval monastery's pottery, on materials from the 12th to 16th centuries excavated in the premonstratensian nunnery in Strzelno - Sułkowska, Krystyna (Religion and belief : a Conference on Medieval Archaeology in Europe, 21-24th September 1992 at the University of York, 1992)
Keywords: strzelno

Kunstschätze des ehemaligen Prämonstratenserinnenklosters Rumbeck - Timmermann, Fritz (Heimatblätter (Arnsberg), 1992)
Keywords: rumbeck

Das Prämonstratenserinnen-Kloster Altenbredelar - Tönsmeyer, Hans Dieter (Marsberg. Ereignisse und Erinnerungen, 1992)
Keywords: bredelar

Die Bulle Unigenitus und die süddeutschen Prämonstratenser - Tüchle, Hermann (Marchtal : Prämonstratenserabtei, Fürstliches Schloß, Kirchliche Akademie; Festgabe zum 300jährigen Bestehen der Stiftskirche St. Peter und Paul (1692 - 1992), 1992)
Keywords: 🇩🇪 germany (general)

Het altaar van Huizingen en de abdijen van Vermand, Terkameren, Ninove en Vicoigne - Van De Perre, Dirk (Analecta Praemonstratensia, 1992)
Keywords: ninove; vermand; vicoigne

Abbaye de Saint-Michael à Anvers - Van den Nieuwenhuizen, Jos (Province d'Anvers, 1992)
Keywords: antwerp

Prieuré de Sainte-Marie-Madeleine à Anvers, puis à Zandvliet - Van den Noortgate, Machteld (Monasticon Belge. Bd. 8: Province d'Anvers, 1992)
Keywords: zandvliet

Het leenhof van de Abdij van Berne - Velden, Gregorius Maria van der (Analecta Praemonstratensia, 1992)
Keywords: berne

Ausgrabungen im Prämonstratenserkloster Windberg 1990 und 1991 - Wojaczek, Christoph (Archäologische Arbeitsgemeinschaft Ostbayern/West- und Südböhmen, 1992)
Keywords: windberg

Die Urkunden des Klosters Oelinghausen - Regesten - Wolf, Manfred (Veröffentlichungen der Historischen Kommission für Westfalen, 1992)
Keywords: oelinghausen

Das ehemalige Kloster Rüti - Wüst, Emil (Jahrheft des Verkehrsvereins Rüti-Tann, 1992)
Keywords: rüti

L'ancienne abbaye de Bellelay: histoire de son architecture - Wyss, Alfred; De Raemy, Daniel (Intervalles, 1992)
Keywords: bellelay